Peran Signifikan Media Sosial Terhadap Pemasaran Produk Kemasan UMKM Pada Daerah Karawang - Hajid Imam Pranoto (Pusat Riset dan Inovasi Nasional, 2023)
The penetration of social media has changed the paradigm of communication and marketing for Micro, Small and Medium Enterprises (MSMEs) in various regions, including in the Karawang Region. This study aims to analyze the significant role of social media in supporting MSMEs in the Karawang Region and understand the benefits obtained by MSMEs in utilizing social media platforms. The research method used is a qualitative approach using in-depth interview techniques with owners and managers of MSMEs who actively use social media as part of their marketing strategy in the Karawang area. The collected data was analyzed using a thematic analysis approach to identify patterns, themes, and the role of social media in the context of MSMEs in the area. The results of the study show that social media plays a significant role in supporting MSMEs in the Karawang Region. MSMEs that use social media report increased brand awareness, wider market reach, and better interaction with customers. Social media provides an affordable, easy-to-use and effective platform for promoting MSME products or services, interacting with customers and obtaining direct feedback. In addition, social media also helps MSMEs in the Karawang Region to gain market insight, follow industry trends, and forge partnerships with local businesses. Another benefit gained is monitoring competitors and developing more effective marketing strategies based on data analysis from social media. This study highlights the importance of using social media in the marketing strategy of MSMEs in the Karawang Region. MSMEs need to use social media wisely to gain significant benefits in improving their performance and competitiveness. However, challenges such as limited digital knowledge and skills and limited internet access need to be overcome through training and support from related parties. This research provides valuable insights for MSMEs in the Karawang Region in understanding the role and benefits of social media in their business context. Local governments and related institutions are expected to provide support in the form of training, digital infrastructure, and access to technology to help MSMEs make optimal use of the potential of social media. Thus, MSMEs in the Karawang Region can increase the success and sustainability of their business in the growing digital era.